Expression-based drug screening of neural progenitor cells from individuals with schizophrenia - Benjamin Readhead (Nature Portfolio, 2018)
Unbiased large scale screening of small molecules for drug discovery in psychiatric disease is technically challenging and financially costly. Here, Readhead and colleagues integrate in silico and in vitro approaches to design and conduct transcriptomic drug screening in schizophrenia patient-derived neural cells, in order to survey novel pathologies and points of intervention.